2010
DOI: 10.1111/j.1365-2036.2009.04167.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of downsizing hepatocellular carcinoma in a liver transplant population

Abstract: SUMMARY BackgroundLong-term results after downstaging hepatocellular carcinoma (HCC) prior to liver transplantation (LT) remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 22 publications
2
66
0
1
Order By: Relevance
“…20,40,41,[55][56][57][58] Two studies treated the total tumor diameter as a continuous variable (the summation of the diameters of all nodules), and both assessed recurrence (HR ¼ 1.19, 95% CI ¼ 0.95-1.49; Table 1). 40,58 Three studies used a cutoff of 10 cm, and they all assessed overall survival.…”
Section: Total Tumor Diametermentioning
confidence: 99%
“…20,40,41,[55][56][57][58] Two studies treated the total tumor diameter as a continuous variable (the summation of the diameters of all nodules), and both assessed recurrence (HR ¼ 1.19, 95% CI ¼ 0.95-1.49; Table 1). 40,58 Three studies used a cutoff of 10 cm, and they all assessed overall survival.…”
Section: Total Tumor Diametermentioning
confidence: 99%
“…Mostly, a predetermined disease stability for 3–6 months after TACE and before enlisting as a candidate is mandatory to select less aggressive tumors that have less chance of posttransplant recurrence. In a long-term follow-up study in patients with HCC initially exceeding the Milan criteria in Korea, it was suggested that patients with a maximum tumor size <7 cm in whom complete necrosis is reached together with AFP levels <100 ng/ml just before LT may be the best candidates for LT following downstaging using TACE [21]. This may contribute to optimizing the management of LT candidates with downsized HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Many groups have validated these criteria [43,44] , but after 5 years, they have not been accepted as widely as the MC. Other authors have made similar suggestions [45] ; however, others have placed this limit at 10 cm, which results in a decrease in DFS [46] . This value should be universally accepted as the upper limit [26] .…”
Section: Importancementioning
confidence: 93%
“…Combined radiological and biological modifications permit documentation of the response to LRT in patients waiting for LT and are essential elements for further refining the selection criteria for potential liver recipients with HCC [94] . An AFP level ≥ 100 ng/mL, a maximum tumor size ≥ 7 cm and a lack of complete necrosis at LT after TACE were found to be independent predictors of HCC recurrence [46] . However, patients with maximum tumor size < 7 cm who achieve complete necrosis together with AFP levels < 100 ng/mL at LT may be the best candidates for LT following downstaging [46] .…”
Section: Response Criteria Following Downstaging With Lrtmentioning
confidence: 99%
See 1 more Smart Citation